Would Firm Performance be Better with Women Directors? Evidence from India. Issue 2 (June 2019) - Jyothi, Pavana; Mangalagiri, Jayasree
The purpose of this article is to examine the impact of women directors on firm performance of Indian companies and to check the impact after controlling their firm-specific and corporate governance variables. Further, the study explores the impact of women directors on firm performance of group firms and standalone firms. Regression models used in the study reveal that women directors create a positive and significant impact on firm performance as measured by return on assets (ROA) and Tobin's Q . Further, the study found that the relationship becomes stronger if a firm belongs to the business group. This article adds to the existing literature on gender diversity at the board level, by analysing the impact of women directors on firm performance in the Indian context. This study is the first to examine the aspect of gender diversity in the Indian context.